“Sadar dan Perangi” Bullying program to reduce bullying intentions of elementary school students: A Quasi-Experimental Study - Hanabella, Rizqi; Febriani, Arum (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: Bullying case is often experienced by school students in Indonesia. Despite existing efforts, such as government regulations and school-based interventions, bullying remains a pervasive issue, highlighting the need for more effective programs.Purpose: This study aimed to test the effectiveness of the 'Sadar dan Perangi’ bullying program in reducing bullying intentions among elementary school students. The program's effectiveness was evaluated based on its ability to lower bullying intentions among participants.Method: The participants were 39 elementary school students in grades 4 and 5 with moderate bullying intentions. This study used a quasi experimental, untreated control group design with dependent pre- and post-test samples. The research instruments used were the Sadar dan Perangi Bullying Program module and the bullying intention scale. In addition, the empathy scale and bullying knowledge were used as manipulation checks. The data were analyzed using a mixed-design ANOVA.Findings: Sadar dan Perangi Bullying Program can reduce bullying intentions of elementary school students in the experimental group (MD=-75; p<0.050).Implication: This study implies that the program has been proven to reduce bullying intention. Therefore, government support is needed to reduce bullying through policy, resource, and budget support for schools